Effect Of Combination Of Ms Media And Growth Regulator Bap On Growth And Development Of Dendrobium mirbelianum Gaudich. Orchid Shoots In Vitro - Varyanti Magdalena Turang; Wenny Tilaar; Jantje Pongoh; Semuel David Runtunuwu; Stella Maria Theresia Tulung; Yefta Pamandungan (Jurnal Agroekoteknologi Terapan, 2023)
Generative propagation of orchids is difficult because orchid seeds do not have endosperm for growth and development, so propagation can be done by in vitro. The growth and development of orchids in vitro can be faster and more efficient compared to conventional methods when combined with the addition of growth regulators into the growing medium of in vitro cultures. MS media is a medium that is often used in in vitro propagation because it has the most complete macro and micro nutrients for plant growth and development, but because the price is fairly expensive, the use of 50% MS media can be a solution to this problem.               This study aims to determine the interaction of the use of MS media composition with ZPT BAP, see the effect of MS media composition on the growth and development of orchid buds, and see the effect of ZPT BAP on the growth and development of orchid buds. This research was conducted at the Biotechnology Laboratory, Faculty of Agriculture, Sam Ratulangi University Manado from March to May 2023. This study used a factorial experiment in a completely randomized design (CRD) with 3 replicates consisting of two factors.. The first factor is MS media composition; MS 100% (A1) and MS 50% (A2) and the second factor is BAP concentration; BAP 0.5 ppm (B1), BAP 1.5 ppm (B2), BAP 2 ppm (B3), and BAP 3 ppm (B4). Data were analyzed by ANOVA and if the effect was significant then continued with 5% BNT test. The variables observed were: Shoot height (cm), number of leaves (strands), number of shoots (units), number of roots (units), and wet weight (g). The results showed that there was an interaction between the treatment of MS media composition and growth regulators on the number of shoots, but there was no interaction on the variable shoot height, number of leaves, number of roots, and wet weight of Dendrobium mirbelianum Gaudich orchid shoots. Keywords: Orchid, Dendrobium mirbelianum, MS media, ZPT BAP, In vitro. Abstrak Perbanyakan anggrek secara generatif sulit dilakukan karena biji anggrek tidak memiliki endosperm untuk pertumbuhan dan perkembangannya, maka dari itu dapat dilakukan perbanyakan dengan cara in vitro. Pertumbuhan dan perkembangan anggrek secara in vitro bisa lebih cepat dan efisien dibandingkan dengan cara konvensional jika dikombinasikan dengan penambahan zat pengatur tumbuh ke dalam media tanam kultur in vitro. Media MS adalah media yang sering digunakan dalam perbanyakan in vitro karena memiliki unsur hara makro dan mikro yang paling lengkap untuk pertumbuhan dan perkembangan tanaman, tetapi karena harganya yang terbilang mahal maka penggunaan media MS 50% dapat menjadi solusi terhadap permasalahan tersebut. Penelitian ini bertujuan untuk mengetahui interaksi penggunaan komposisi media MS dengan ZPT BAP dan mendapatkan kombinasi perlakuan yang paling baik terhadap pertumbuhan dan perkembangan tunas anggrek. Penelitian ini dilaksanakan di Laboratorium Bioteknologi, Fakultas Pertanian, Universitas Sam Ratulangi Manado dari bulan Maret sampai Mei 2023. Penelitian ini menggunakan percobaan faktorial dalam Rancangan Acak Lengkap (RAL)  dengan 3 ulangan yang terdiri dari dua faktor. Faktor pertama yaitu komposisi media MS; MS 100% (A1) dan MS 50% (A2) dan faktor kedua konsentrasi BAP; BAP 0,5 ppm (B1), BAP 1,5 ppm (B2), BAP 2 ppm (B3), dan BAP 3 ppm (B4). Data dianalisis dengan ANOVA dan jika berpengaruh nyata maka dilanjutkan dengan uji BNT 5 %. Variabel yang diamati adalah: Tinggi tunas (cm), jumlah daun (helai), jumlah tunas (unit), jumlah akar (unit), dan berat basah (g). Hasil penelitian menunjukkan bahwa terdapat interaksi antara perlakuan komposisi media MS dan zat pengatur tumbuh terhadap jumlah tunas, tetapi tidak terdapat interaksi pada variabel tinggi tunas, jumlah daun, jumlah akar, dan berat basah tunas anggrek Dendrobium mirbelianum Gaudich. Kata Kunci: Anggrek, Dendrobium mirbelianum, media MS, ZPT BAP, In vitro